Balanced 10% hydroxyethyl starch compared with balanced 6% hydroxyethyl starch and balanced crystalloid using a goal-directed hemodynamic algorithm in pancreatic surgery: A randomized clinical trial. Issue 17 (April 2018) - Werner, Julia; Hunsicker, Oliver; Schneider, Anja; Stein, Henryk; von Heymann, Christian; Freitag, Adrian; Feldheiser, Aarne; Wernecke, Klaus-Dieter; Spies, Claudia
Abstract: Background: While hydroxyethyl starch (HES) solutions are not recommended any longer in critically ill patients, data on efficacy and safety during surgery are still limited. Methods: In a randomized controlled trial 63 patients were assigned to receive 10% HES (130/0.42), 6% HES (130/0.42), or crystalloid within a goal-directed hemodynamic algorithm during pancreatic surgery. The primary endpoints were intraoperative volume of HES and time until fully on oral diet. Results: The trial was terminated early upon recommendation of an independent data monitoring committee due to futility for efficacy at a planned interim analysis. The intraoperative volume of HES was not different between 10% and 6% HES group (2000 [1500; 2250] vs 2250 [1750; 3000] mL, P= .059). However, considering an inhomogeneity of patient's body weight between HES groups, there was a significant difference in intraoperative volume of HES between 10% and 6% group after adjusting for patient's body weight (24.0 [21.6; 28.3] vs 33.3 [28.2; 46.2] mL kg −1 BW, P = .002). Patients in the HES groups required less additional fluid after dose limit than those in the crystalloid group, resulting in lower intraoperative net balances. The time until fully on oral diet was not different between all study groups. Applying KDIGO oliguria criterion, patients receiving 10% HES had more AKI compared to patients receiving crystalloids (86.7 vs 45.0%, P = .010), whereas those receiving 6% HES and crystalloids did not differ (58.8 vs 45.0%, P = .253). Further explorative analyses using a gray-zone approach indicated that patients receiving 6% HES below 18.8 mL kg −1 will not experience AKI with near certainty. Conclusions: After adjusting for patient's body weight, patients receiving 6% HES required more volume of HES than patients receiving 10% HES. The relation of 140% represents very well the volume effect of a hyperoncotic 10% HES solution. Nonetheless, both HES solutions were similarly effective in reducing intraoperative fluid administration compared with crystalloid, but this did not result into differences in gastrointestinal outcomes. Patients receiving 10% HES showed an increased rate of AKI, whereas those receiving 6% HES and crystalloid did not differ. However, 6% HES should not be applied beyond 18 mL kg −1 during surgery. Abstract : Supplemental Digital Content is available in the text